Jennifer's diary - Fine, Anne.; Aldous, Kate; Puffin Books (London : Puffin Books, 1996)
Although Jennifer is stumped for ideas to use in her new diary, her friend Iola is bursting with stories that may or may not be true to write down if only she had that lovely rainbow-colored book!
3.0
K-3
K-3
Keywords: Authorship -- Juvenile fiction; Diaries -- Juvenile fiction; Authorship -- Fiction; Diaries -- Fiction; Authorship -- Fiction; Diaries -- Fiction